Methods of application and doses of inoculation with Azospirillum in agronomic performance of off-season corn crop - Fiorini, Ivan Vilela Andrade; Pereira, Cassiano Spaziani; Schoffen, Mateus Emanuel; Tonial, Mauricio Escobar; Sabino, Daniele Cristina Costa; Silva, Adriano Alves da (Revista Agrogeoambiental, 2020)
In order to achieve high yields for off-season corn crop sown after soybean harvest, high doses of nitrogen fertilizers are required. Biological nitrogen fixation helps reduce the use of nitrogen fertilizers through the inoculation of nitrogen-fixing associative bacteria, such as those of the genus Azospirillum. This study aimed to evaluate the agronomic performance of corn hybrid DKB390Y in response to different application methods, such as using inoculant and doses of inoculant with Azospirillum brasilense. The experiment was conducted in a property adjacent to Federal University of Mato Grosso (Sinop campus), between February and July 2018. The experimental design included randomized blocks in a 3×5 factorial arrangement, replicated four times (with three application methods: foliar spraying; spraying foliar with bovine gelatin; and with a paint roller (Black & Decker Rapid Roller BDPR400-wool®) and five doses of inoculant: 0, 100, 200, 400 and 800 mL ha-1). No significant differences were obtained through the application methods in the rates of chlorophyll, plant height, stem diameter, number of rows of grains, number of grains per row, ear length, ear diameter and weight of one thousand grains, except for grain yield. Grain yield was found to be superior with foliar inoculation at 100 mL ha-1 method foliar spray, and 200 mL ha-1 at method foliar application with bovine gelatin.